Genetic Variability within the Murgese Horse Breed Inferred from Genealogical Data and Morphometric Measurements - Grazia Bramante; Elisa Pieragostini; Elena Ciani (Diversity, 2022)
The Murgese horse (MH) is a native breed from Apulia (Italy). This study aimed to evaluate the population status with regard to the available pedigree information (6923 animals born between 1900 and 2020), as well as its demographic and morphological evolution. The mean equivalent generations were 5.88. The average relatedness, inbreeding coefficient and increase in inbreeding by equivalent generation (ΔF) were 9.88%, 5.22%, 1.05%, respectively. The effective population size based on ΔF was 47.46. The effective number of founders (fe) was 36, and that of ancestors (fa) was 19. The ratio fe/fa was 1.89 witnessing a bottleneck effect. The ratio fa/fe indicates a 52% reduction of the genetic diversity as expected, given the fact that, for the current population (now recovered to 5000 breeding animals), the fe is 34 and the fa only 17, with 50% of diversity being explained by only six ancestors. Basically, the results reflect a substantial loss of genetic diversity in the MH breed over generations since its official founding, and unbalanced use of sires in the population, highlighting the importance of continuous monitoring and implementation of more effective conservation measures, especially in view of the growing request for boosting genetic improvement for MH morpho-functional traits.